2013
DOI: 10.1111/ics.12064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between fibroblasts and mesenchymal stem cells derived from dermal and adipose tissue

Abstract: Human dermal fibroblasts have a potential to adhere to plastic surfaces and differentiate into other cell types. However, for stem cells intended to be used in cosmetics, experiments conducted with contaminated fibroblasts may produce poor or even falsely negative results for the efficacy of the active ingredient or formulation and thus conceal their promising effects as anti-ageing and skin rejuvenation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 56 publications
2
40
1
Order By: Relevance
“…They differ on the basis of hundreds of DE genes, as evaluated by the analyses of mRNAs associated with the translation machinery. We also show that, contradicting repeated previous suggestions [1,[3][4][5][6][7], fibroblasts are not able to differentiate into adipocytes, osteoblasts, or condrocytes. We believe that the residual differentiation previously described was due to the fact that it is very difficult to obtain pure populations of dermal fibroblasts, as also suggested by Lennon et al [29].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…They differ on the basis of hundreds of DE genes, as evaluated by the analyses of mRNAs associated with the translation machinery. We also show that, contradicting repeated previous suggestions [1,[3][4][5][6][7], fibroblasts are not able to differentiate into adipocytes, osteoblasts, or condrocytes. We believe that the residual differentiation previously described was due to the fact that it is very difficult to obtain pure populations of dermal fibroblasts, as also suggested by Lennon et al [29].…”
Section: Discussioncontrasting
confidence: 89%
“…MSCs self-renew and retain a multipotent differentiation capacity, whereas fibroblasts seem to display only limited, or no such, multipotent differentiation [2], although there is controversy in the literature over this issue. Indeed, it has been suggested that fibroblasts are able to differentiate [1,[3][4][5][6][7] and could be used in cell therapy [8]. Recently, Blasi et al [3] reported that fibroblasts may differentiate but lack anti-inflammatory and angiogenic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that fibroblasts from human bronchus, dermis, and foreskin are similar to bone marrow-derived MSCs in regard to their cell surface markers [16,17,4346]. Many reports have also demonstrated the ability of fibroblasts from different tissues, including dermis, lung, and orbit, to differentiate into adipocytes, chondrocytes, and osteoblasts [1619,43,45,4749]. Furthermore, dermal and foreskin fibroblasts have been shown to be suppress T cell proliferation [20,23,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Dermal fibroblasts are considered to be mature mesenchymal cells and are particularly abundant in the connective areas of each organ and tissue [48]. Moreover, it has been reported that MSC and fibroblasts share many characteristics in differentiation, proliferation potential, distribution, phenotype and immunoregulation [48,49]. A slight but statistically significant decrease in cell growth was only observed in HDF 106 cells treated alone 24 h after SW exposure.…”
Section: Discussionmentioning
confidence: 99%